(untitled) (Bangladesh Journal of Animal Science, 2022)
The popular summer cereal fodder is Teosinte (Euchlaena mexicana) which has low productivity and chemical constituents. The quality and quantity of teosinte fodder can be enhanced by adjusting cultivation practices including use of appropriate sowing dates and by following an appropriate mixed cropping cultivation with legumes. This study was conducted to identify the fodder quantity and quality under a commonly practiced mixed cultivation of legumes with teosinte with varied sowing dates. Three combination of fodder; teosinte, teosinte+cowpea and tesosinte+rice bean was arranged in four sowing dates in Split Plot Design, replicated five times. Sowing dates were arranged as main plot while combination of fodder species was arranged as sub plot. Growth parameters of teosinte (tiller numbers/m2, plant height), green herbage mass, dry herbage mass, crude protein (CP), acid detergent fiber (ADF) and neutral detergent fiber (NDF) were determined. The results showed significantly highest (p<0.05) cumulative green and dry herbage mass was obtained from teosinte+cowpea, if sown in 18th April followed by 28th April for the same combination of treatments. Significantly the highest (p<0.001) average value of CP was obtained from teosinte+cowpea whereas the highest (p<0.001) average value of NDF and ADF were obtained from teosinte mono crop. The effect of date of sowing and treatments interaction/combination on average value of CP, NDF and ADF were statistically similar (p>0.05). The result of this experiment indicated that teosinte sown with cowpea in 18th April might be the best combination to produce high herbage mass as well as better quality of fodder. Bangladesh Journal of Animal Science. 2022. 51 (2): 47-54